Effects of Frailty Syndrome on Osteoporosis, Focusing on the Mediating Effect of Muscle Strength and Balance in Community-Dwelling Older Adults (≥60 years) in Iran: Results From the Amirkola Health and Aging Project Cohort Study - Abbas Shamsalinia; Seyed Reza Hosseini; Ali Bijani; Reza Ghadimi; Mohammad Reza Kordbageri; Kiyana Saadati; Fatemeh Ghaffari (Geriatric Orthopaedic Surgery & Rehabilitation, 2024)
Introduction For older adults, maintaining muscle strength and balance is crucial to preserve an upright posture and independently manage their basic activities of daily living (ADL). This study aimed to examine whether muscle strength and balance mediate the relationship between frailty syndrome (FS) and osteoporosis in a large sample of community-dwelling older adults. Material and Methods This cross-sectional study is part of the second phase (2016-2017) of the Amirkola Health and Ageing Project (AHAP), a cohort study conducted on all elderly aged 60 and over in Amirkola, Northern Iran, since 2011. Data from 2018 older adults were collected by a trained person using bone mineral density (BMD), frailty index, activities of daily living (ADL), instrumental activities of daily living (IADL), handgrip strength (HGS), quadriceps muscle strength (QMS), Berg Balance Scale (BBS), and Timed Up and Go test (TUG test) and analyzed using analysis of variance, chi-square, and path analysis tests. Results The mean indices of femoral neck BMD and lumbar spine BMD, HGS, QMS, BBS, ADL, and IADL were lower in the frail older adults than in the pre-frail and non-frail older adults. In addition, the mean TUG test level was higher in the frail older adults than in the non-frail and pre-frail older adults. The results of the present study have indicated that frailty is significantly related to osteoporosis, and that balance and muscle strength can predict osteoporosis; these variables play a mediating role in the relationship between frailty and osteoporosis. Conclusion From the results of the present study, it can be concluded that frailty may increase the odds of osteoporosis. The results of the current study have indicated that balance (BBS and TUG test) and muscle strength (HGS and QMS) are associated with osteoporosis and these variables play a mediating role in the relationship between frailty and osteoporosis.